A Survey on Awareness of Fixed Dose Combinations (FDCs) among Patients, Physicians and Pharmacists at Pune and Beed (India) - PJ, Patil; MJ, Patil; VR, Patil; TA, Deshmukh; SS, Band (Indian Journal of Pharmacy Practice)
Fixed dose combinations (FDCs) of pharmaceutical products are flourishing in the Indian pharmaceutical market. It was found out that many FDCs were irrational. In consequence to that, some FDCs have been withdrawn from the market. This paper aims to evaluate awareness about the FDC among patient, pharmacist and physicians and to create awareness in society in general. Also, opinion regarding rationality and safety of FDCs were determined. Three different questionnaires containing different questions were prepared for patient, pharmacist and physicians. Surveys were conducted among patients (n=50), pharmacists (n=55) and physicians (n=40). Questionnaires having different questions were presented to respective personnel individually. Collected data was tabulated and percentage responses were compared. It was found that there was contrast in the thinking of physician and pharmacist vs patient on rationality of FDCs. Majority of the physicians and pharmacists thought that FDCs are rational, whereas patients thought FDCs as irrational. In general, it was found out that there was no specific storage condition for FDCs as compared to single drug formulation. Physicians and pharmacists agreed that FDCs are more convenient to patient, whereas there is tie on these issues among patients. All physicians, pharmacists and patients unanimously agreed on the issue that FDCs are more cost effective than single drug.
Keywords: Awareness; Fixed dose combinations; Patients; Pharmacists; Physicians; Rational Drug Therapy; survey